Economic Analysis and Resource Use Efficiency of Cotton Production in Haryana (Indian Journal of Extension Education, 2023)
The study was conducted on the economic analysis of cotton crop and its returns in two districts viz. Sirsa and Hisar of Haryana selected purposely having the highest area. The collected data was used to calculate the cost and returns and resource use efficiency of cotton crop in Haryana. The cost benefit ratio for the study area came out as 1:1.22, 1:1.04 and 1:1.13 Sirsa, Hisar and overall, respectively. The findings concluded that resource use efficiency of the cotton farms is showing decreasing returns to scale in both Sirsa (0.419) and Hisar (0.413) districts, which means that there is no scope for improvement in the yield of cotton and there is over-utilization of the resources for the cotton cultivation in Haryana.